Liver dysfunction among workers handling 5-nitro-o-toluidine - Shimizu, H; Kumada, T; Nakano, S; Kiriyama, S; Sone, Y; Honda, T; Watanabe, K; Nakano, I; Fukuda, Y; Hayakawa, T (Gut, 2002)
Background: 5-Nitro-o-toluidine is an aromatic nitro amino compound. While other aromatic compounds are known to damage the human liver and are registered as toxic substances, toxicity information concerning 5-nitro-o-toluidine is lacking. Aims: To investigate the hepatotoxicity of 5-nitro-o-toluidine. Patients and methods: Of 15 workers in the same factory who handled 5-nitro-o-toluidine, three were hospitalised with symptoms of acute liver dysfunction. Suspecting a link between liver dysfunction and working conditions, we correlated workplace factors with clinical findings in all 15 workers. Results: Blood biochemistry tests indicated liver damage in seven of 15 study subjects. Workers who handled 5-nitro-o-toluidine and nitrosyl sulphuric acid often loosened their respiratory protective equipment shortly after 5-nitro-o-toluidine powder had been dispersed into the air of the room. No potential hepatotoxins were present except for 5-nitro-o-toluidine. Six of the affected workers had handled 5-nitro-o-toluidine 12 to 20 times; the seventh worker had handled the powder three times; and the other eight workers without liver dysfunction had handled the material once or twice. No other significant differences in background were evident between the affected and unaffected workers, such as age, sex, or protective measures. Histological findings during recovery from liver damage were similar to those of acute viral hepatitis. None of the 15 subjects has demonstrated liver damage since the factory was closed. Conclusions: A link between liver dysfunction and 5-nitro-o-toluidine exposure is suggested by greater severity of liver dysfunction associated with more episodes of handling.